2015
DOI: 10.2466/15.20.pr0.117c29z0
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Stress and Recovery as Concurrent Predictors of the Affect Balance of Patients with Fibromyalgia

Abstract: This study examined sources of stress and recovery in a group of 107 patients with fibromyalgia (M age = 50.4 yr., SD = 11.8), in comparison to a control group of 68 healthy participants (M age = 47.8 yr., SD = 8.1) of equivalent age and marital status. Between-group differences in sources of stress and recovery were examined by means of an independent samples t test. In addition, between-groups differences in the relationship between sources of stress and recovery and affect balance were explored through a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The affect balance of MCI empty‐nest older adults is lower than non‐MCI empty‐nest older adults. According to González et al , there is a strong correlation between sources of stress and recovery and affect balance . It has been accepted that positive affect provides a protective effect with respect to mental health .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The affect balance of MCI empty‐nest older adults is lower than non‐MCI empty‐nest older adults. According to González et al , there is a strong correlation between sources of stress and recovery and affect balance . It has been accepted that positive affect provides a protective effect with respect to mental health .…”
Section: Discussionmentioning
confidence: 99%
“…According to González et al, there is a strong correlation between sources of stress and recovery and affect balance. 24 It has been accepted that positive affect provides a protective effect with respect to mental health. 16 In China, the incidence rate of negative affect, especially depressive symptoms among empty-nest older adults, is much higher than for any other aged individual groups.…”
Section: Discussionmentioning
confidence: 99%
“…In stress-related contexts, the perception of threat can be fed by an unremitting flow of daily concerns, worries and hassles [60][61][62] , derived from the person's inner and outer world. Other personality, cognitiveaffective and social factors, such as neuroticism 63 , perseverative thinking 60,61 , pain catastrophizing 64 , unbalanced affect and limited adaptive resources [65][66][67][68][69][70] , as well as unsupportive social environments 46,47 , can contribute to minimizing safeness and augment perceptions of threat. A qualitative study of a small group of women with fibromyalgia reported that participants exhibited "signs of a threatening world of experiences" 71 .…”
Section: Perspectivementioning
confidence: 99%
“…Schimmack (2008) defined affect balance as positive minus negative affect. Several studies have since explored affect balance (Gonzalez et al, 2015;Liu et al, 2013;Sirois & Hirsch, 2015;Zhu, 2015). Lui et al (2013) found that higher scores for affect balance in part mediated the relationship between emotional intelligence and increased subjective well-being.…”
mentioning
confidence: 99%
“…Affect balance refers to the overall emotional wellbeing of an individual which incorporates both positive and negative feelings (Gonzalez et al, 2015;Sirois & Hirsch, 2015;Zhu, 2015). The Positive Affect Negative Affect Scale (PANAS; Watson et al, 1988) measures positive and negative affect.…”
mentioning
confidence: 99%